2013
DOI: 10.3389/fphys.2013.00379
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic myopathy: impact of diabetes mellitus on skeletal muscle progenitor cells

Abstract: Diabetes mellitus is defined as a group of metabolic diseases that are associated with the presence of a hyperglycemic state due to impairments in insulin release and/or function. While the development of each form of diabetes (Type 1 or Type 2) drastically differs, resultant pathologies often overlap. In each diabetic condition, a failure to maintain healthy muscle is often observed, and is termed diabetic myopathy. This significant, but often overlooked, complication is believed to contribute to the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 101 publications
(121 reference statements)
4
158
2
7
Order By: Relevance
“…We have shown that nitrate increases muscle -oxidation and mitochondrial biogenesis (23), and therefore may have utility in treating the intramuscular lipid deposition-induced lipotoxicity and insulin resistance associated with diabetes. However, diabetic myopathy is a major complication of diabetes and is characterized by muscle atrophy and reduced physical performance and muscle capacity (20). Skeletal muscle from diabetic patients exhibits a higher concentration of glycolytic fibers (38), and evidence of a switch towards a glycolytic phenotype (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that nitrate increases muscle -oxidation and mitochondrial biogenesis (23), and therefore may have utility in treating the intramuscular lipid deposition-induced lipotoxicity and insulin resistance associated with diabetes. However, diabetic myopathy is a major complication of diabetes and is characterized by muscle atrophy and reduced physical performance and muscle capacity (20). Skeletal muscle from diabetic patients exhibits a higher concentration of glycolytic fibers (38), and evidence of a switch towards a glycolytic phenotype (39).…”
Section: Discussionmentioning
confidence: 99%
“…5 Exercise is an effective intervention for both the prevention and treatment of type 2 diabetes mellitus (T2DM) (19). Diabetic myopathy, characterized by reduced muscle functional capacity, atrophy and a glycolytic fiber-type, is a major diabetic complication (20). Furthermore, the proportion of type I fibers in muscle is positively correlated with systemic insulin sensitivity (21); and decreased levels of type I fibers are associated with insulin resistant states including T2DM (22).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite cells are well acknowledged targets of diabetes-induced damage and contributors of diabetic vascular myopathy (7)(8)(9)(10). Recent evidence indicates pericytes play key role in vascular and muscular regeneration (11)(12)(13) and have potential to become favorite candidates for cell therapy of PAD and myocardial ischemia (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In skeletal muscles, insulin promotes glucose uptake by stimulating a cascade of signaling processes initiated by the binding of insulin to the extracellular α-subunit of the IR on the cellular membrane (D'Souza et al, 2013). After binding, the intracellular tyrosine kinase domain of the IR becomes activated by IR autophosphorylation of its intracellular β-subunit.…”
Section: Discussionmentioning
confidence: 99%